MusE GAs FLOw and Wind (MEGAFLOW) IX. The impact of gas flows on the relations between the mass, star formation rate, and metallicity of galaxies. Issue 1 (1st January 2023) - Langan, Ivanna; Zabl, Johannes; Bouché, Nicolas F; Ginolfi, Michele; Popping, Gergö; Schroetter, Ilane; Wendt, Martin; Schaye, Joop; Boogaard, Leindert; Freundlich, Jonathan; Richard, Johan; Matthee, Jorryt; et al.
ABSTRACT: We study the link between gas flow events and key galaxy scaling relations: the relations between star formation rate (SFR) and stellar mass (the main sequence, MS); gas metallicity and stellar mass (the mass–metallicity relation, MZR); and gas metallicity, stellar mass, and SFR (the fundamental metallicity relation, FMR). Using all star-forming galaxies (SFGs) in the 22 MUSE fields of the MusE GAs FLOw and Wind (MEGAFLOW) survey, we derive the MS, MZR, and FMR scaling relations for 385 SFGs with M_= 10^8 - 10^11.5 M_ at redshifts 0.35 < z < 0.85. Using the MUSE data and complementary X-Shooter spectra at 0.85 < z < 1.4, we determine the locations of 21 SFGs associated with inflowing or outflowing circumgalactic gas (i.e. with strong Mg ii absorption in background quasar spectra) relative to these scaling relations. Compared to a control sample of galaxies without gas flows (i.e. without Mg ii absorption within 70 kpc of the quasar), SFGs with inflow events (i.e. Mg ii absorption along the major axis) are preferentially located above the MS, while SFGs with outflow events (i.e. Mg ii absorption along the minor axis) are preferentially more metal rich. Our observations support the scenario in which gas accretion increases the SFR while diluting the metal content and where circumgalactic outflows are found in more metal-rich galaxies.